2015
DOI: 10.1063/1.4935440
|View full text |Cite
|
Sign up to set email alerts
|

A study of cooling process in bulk metallic glasses fabrication

Abstract: To study the temperature distribution and evolution during bulk metallic glasses fabrication, finite element method was taken to simulate the cooling process in glassy alloys fabricated by water quenching and copper mold casting. The temperature distribution and evolution in different-sized samples in the two methods were successfully reproduced. The result showed that the temperature distribution in the alloy was strongly affected by fabricating method. Two relations were then proposed to estimate the cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…The final state of the cast rod depends on a number of factors, including casting temperature T cast , mold temperature T mold , rod diameter, thermal conductivity and thickness of the mold material, and the heat transfer coefficient between the cast rod and the mold. For the same Zr-based composition, it was confirmed that the formation of a number of eutectoid phases or a fully amorphous structure depends only on T cast . In our case, increasing T cast leads to the formation of two martensitic CuZr phases ( Cm and P 2 1 / m ) and CuZr 2 crystals in rods of 2 and 3 mm diameter (Figure S6).…”
Section: Discussionsupporting
confidence: 55%
“…The final state of the cast rod depends on a number of factors, including casting temperature T cast , mold temperature T mold , rod diameter, thermal conductivity and thickness of the mold material, and the heat transfer coefficient between the cast rod and the mold. For the same Zr-based composition, it was confirmed that the formation of a number of eutectoid phases or a fully amorphous structure depends only on T cast . In our case, increasing T cast leads to the formation of two martensitic CuZr phases ( Cm and P 2 1 / m ) and CuZr 2 crystals in rods of 2 and 3 mm diameter (Figure S6).…”
Section: Discussionsupporting
confidence: 55%
“…The cooling rate of a plate can be estimated from the finite element modeling of the BMG ingots fabricated by the copper mold casting, where the obtained cooling rates of samples were in a linear agreement with the variation of sample diameter [66]. For the plate geometry, the equation to obtain the cooling rate was slightly modified as:…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are temperature dependent. The thermodynamic parameters of the copper mold were set as 400 W/(m•K) for k, 8.9 g/cm 3 for ρ, and 0.39 J/(g•K) for C p , respectively [24]. According to the Archimedes principle, ρ of the Fe-based BMG was about 7.461 g/cm 3 .…”
Section: Numerical Modelmentioning
confidence: 99%